2006
DOI: 10.1152/ajpcell.00226.2005
|View full text |Cite
|
Sign up to set email alerts
|

Store-operated Ca2+ entry modulates sarcoplasmic reticulum Ca2+ loading in neonatal rabbit cardiac ventricular myocytes

Abstract: Store-operated Ca2+ entry (SOCE), which is Ca2+ entry triggered by the depletion of intracellular Ca2+ stores, has been observed in many cell types, but only recently has it been suggested to occur in cardiomyocytes. In the present study, we have demonstrated SOCE-dependent sarcoplasmic reticulum (SR) Ca2+ loading (load(SR)) that was not altered by inhibition of L-type Ca2+ channels, reverse mode Na+/Ca2+ exchange (NCX), or nonselective cation channels. In contrast, lowering the extracellular [Ca2+] to 0 mM or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
47
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 44 publications
10
47
1
Order By: Relevance
“…It should be noted, however, that Gd 3ϩ is a nonspecific cation channel inhibitor; therefore interpretation of results based on Gd 3ϩ need to be made with caution. Nevertheless, these data support earlier findings of Huang et al (36) who showed that in neonatal rabbit cardiomyocytes increased SR Ca 2ϩ content and resultant arrhythmic activity could be attenuated by SKF96365. In addition, TRPC channel expression and SOCE have both been shown to occur in pacemaker cells such as those of the sinoatrial node (41,105).…”
Section: Potential Role For Stim1-mediated Soce In Ischemia/reperfusisupporting
confidence: 92%
“…It should be noted, however, that Gd 3ϩ is a nonspecific cation channel inhibitor; therefore interpretation of results based on Gd 3ϩ need to be made with caution. Nevertheless, these data support earlier findings of Huang et al (36) who showed that in neonatal rabbit cardiomyocytes increased SR Ca 2ϩ content and resultant arrhythmic activity could be attenuated by SKF96365. In addition, TRPC channel expression and SOCE have both been shown to occur in pacemaker cells such as those of the sinoatrial node (41,105).…”
Section: Potential Role For Stim1-mediated Soce In Ischemia/reperfusisupporting
confidence: 92%
“…It has been suggested that neonatal mammalian ventricular myocytes have a relatively sparse and immature SR compared with that in adults (11,25), but recent studies indicate that a prominent SR Ca 2ϩ accumulation can take place in neonatal myocytes (12,13,21). Here we have attempted to identify, quantify, and compare the mechanisms contributing to load SR in neonatal and adult hearts.…”
Section: Discussionmentioning
confidence: 99%
“…The Simon Fraser University Animal Care Committee approved the use of animals and the experimental protocol used in this study in accordance with CCAC regulations. Ventricular myocytes were isolated from the hearts of New Zealand White rabbits (of either sex) from four distinct age groups, 3 (3d), 10 (10d), 20 (20d), and 56 (56d) days postpartum, by methods previously described (12,13,17).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations